Relationships Of Physical Change With Anxiety Levels In Menopause Women - Hariyanti Haris; Alfira, Nadia; Anggi Angriani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
According to WHO data (world health organization), the population of women experiencing menopause worldwide reached 645 million people and in 2010 it increased to 894 million people and in 2015 the number of menopause women increased by 500 million people is expected to increase by 2030 1, as many as 1,2 billion people. This study is an analytic observational study with a cross-sectional approach that aims to analyze the relationship of physical changes women in the lion village of herlang distict, Bulukumba district. The population in this study were post-menopause women in lion village herlang district, bulukumba district which was 232 respondents, the sample of this study amounted to 47 people taken using the unpaired comparative, comparative analytic formula, data analysis using alternative chi-square test Kolmogorov with p= value 0,05 the result of the study showed that physical changes, changed as many as 40 respondents (85,1%) while the unchanged were 7 respondents (14,9%). From the result of severe anxiety levels, there are 23 respondents (48,9%), mild anxiety as many as 17 respondents (36,2%), while moderate anxiety 7 respondents (14,9%). The conclusion is that there is a relationship between physical changes and the level of anxiety in menopause women in the lion village, herlang district bulukumba district. It is recommended that the result of this study is used as scientific reading as reference material for students who study similar problems.